The Harriet Lane handbook - Tschudy, Megan; Arcara, Kristin; JOHNS HOPKINS HOSPITAL CHILDREN'S MEDICAL AND SURGICAL CENTER (St. Louis, Mo. ; ELSEVIER : Mosby, 2011)
Describe el enfoque diagnóstico de varios tipos de exantemas. se ha incluido nuevos capítulos de medicina basada en la evidencia. También se ha hecho un intento de incluir fuentes de internet al inicio de los capítulos si se dispone de las mismas para facilitar la actualización y la profundización en la información clínica.
Part I: Pediatric Acute Care 1. Emergency Management 2. Poisonings 3.Procedures 4. Trauma, Burns, and Common Critical Care Emergencies Part II: Diagnostic and Therapeutic Informatio 5. Adolescent Medicine; 6. Analgesia and Sedation; Cardiology; Dermatology; Development, Behavior and Mental Health; Endocrinology; Fluids and Electrolytes; Gastroenterology; Genetics; Hematology; Immunology and Allergy; Immunoprophylaxis; Microbiology and Infectious Disease; Neonatology; Nephrology; Neurology; Nutrition and Growth; Oncology; Palliative Care; Pulmonology; Radiology; Rheumatology Part III: Reference-Blood Chemistries and Body Fluids; Biostatistics and Evidence-Based Medicine Part IV: Formular Drug Doses; Formulary Adjunct; Drugs in Renal Failure
Includes Internet access.
The Harriet Lane Service Childrent s Medical an Surgical Center of The Johns Hopkins Hospital
Incluye with more than 110 ilustrations and over 55 color plates
Keywords: PEDIATRÍA -- MANUALES; HANDBOOKS AND MANUALS -- FAST